Pengaruh Infrastruktur, Indek Pembangunan Manuia dan Korupsi terhadap Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat di Indonesia - Lusi Defianti; Hasdi Aimon; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This research aims to determine the effect of (1) infrastructure and human development index on economic growth in Indonesia, (2) human development index and corruption on community’s prosperity in Indonesia, (3) economic growth on the prosperity of the community in Indonesia by using the simultaneous equation method with the Indirect Least Square Model and panel data from 2014 to 2018. The estimates of this research show that (1) the infrastructure has no significant effect on economic groeth in Indonesia (2) the human development index has a positive significant effect on economic growth in Indonesia (3) the human development index has a positive significant effect on the prosperity of community in Indonesia (4) the corruption does not have a significant effect on the prosperity of community in Indonesia (5) the economic growth has a positive significant effect on the prosperity of community in Indonesia.